2012
DOI: 10.1021/jp211648x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hydroxyapatite Hierarchical Hollow Microspheres and Potential Application in Water Treatment

Abstract: Many efforts have been made in fabricating three-dimensional (3D) ordered hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HAp) nanostructures due to their growing applications as a bone cement, drug deliverer, tooth paste additive, dental implant, gas sensor, ion exchange, catalyst, etc. Here, we developed a new synthetic route to 3D HAp-based hollow microspheres through a water-soluble biopolymer (polyaspartic acid) assisted assembly from HAp nanorods. The as-obtained products were characterized by Xray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(89 citation statements)
references
References 61 publications
0
86
0
Order By: Relevance
“…For examples, Nathanael et al [164] reported a template-free formation of HAp nanorings with an inner diameter of 70 nm by a combined high gravity and hydrothermal crystal growth approach. Jiang et al [165] reported a template-free route to fabricate nanostructured hollow HAp microspheres assembled with nanorods (50 nm in thickness, 0.5-1 µm in length) by hydrothermal approach using poly(aspartic acid) as both a chelating and a capping agent. Ma and Zhu [166] reported the fabrication of hierarchically nanostructured HAp hollow spheres (assembled from nanorods) using solvothermal method at 200…”
Section: Hydrothermal Crystal Growthmentioning
confidence: 99%
“…For examples, Nathanael et al [164] reported a template-free formation of HAp nanorings with an inner diameter of 70 nm by a combined high gravity and hydrothermal crystal growth approach. Jiang et al [165] reported a template-free route to fabricate nanostructured hollow HAp microspheres assembled with nanorods (50 nm in thickness, 0.5-1 µm in length) by hydrothermal approach using poly(aspartic acid) as both a chelating and a capping agent. Ma and Zhu [166] reported the fabrication of hierarchically nanostructured HAp hollow spheres (assembled from nanorods) using solvothermal method at 200…”
Section: Hydrothermal Crystal Growthmentioning
confidence: 99%
“…However, the nature of the granules in amorphous state is obscure. The granules can also be amorphous calcium phosphate (Jiang et al 2012), which is a common precursor of crystalline HAPs. It is not easy to judge whether they are inorganics or undissolved organics when they intergrowth with crystalline solid.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30] The broadened diffraction peaks of Co-Al LDH indicate that the synthetic sample is composed of nanocrystals. 31 Compared the m-SiO2, Co-Al LDH and m-SiO2@Co-Al LDH wide-angle XRD patterns, two relatively weak peaks of m-SiO2@Co-Al LDH at around can be assigned to (003) and (012) of layered Co-Al LDH structure ( Figure 3A). Moreover, the (006) peak of Co-Al LDH and the broad peak between 20 o and 25 o of m-SiO2 were overlapping, so the broad peak of m-SiO2 may cover the weak (006) peak of Co-Al LDH in the m-SiO2@Co-Al LDH structure.…”
Section: Characterization Of M-sio2@co-al Ldhmentioning
confidence: 99%